2001
DOI: 10.1080/165019701750300591
|View full text |Cite
|
Sign up to set email alerts
|

Disabilities in Children With Duchenne Muscular Dystrophy: A Profile

Abstract: Proper assessment of disabilities is essential for rehabilitation of patients with Duchenne muscular dystrophy. The aim of this study was to identify and quantify the disabilities in children with Duchenne muscular dystrophy and correlate them with impairment. Thirty-one patients with Duchenne muscular dystrophy of age four years and above were studied. The motor functions were evaluated using total motor score, upper and lower extremity function grades and timed function tests. Disability was quantified with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 10 publications
(12 reference statements)
1
31
1
14
Order By: Relevance
“…In the present study, the children had to use hip compensatory movements (lateral elevation, internal rota tion, abduction) and also trunk support on the handrail to climb up steps. Sivaraman et al 17 reported that ankle dor sal and plantar flexion are the most important movements when climbing down steps. This makes this task particular ly difficult for children with DMD, who usually have equinus gait and/or reduced range of motion and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the children had to use hip compensatory movements (lateral elevation, internal rota tion, abduction) and also trunk support on the handrail to climb up steps. Sivaraman et al 17 reported that ankle dor sal and plantar flexion are the most important movements when climbing down steps. This makes this task particular ly difficult for children with DMD, who usually have equinus gait and/or reduced range of motion and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on scales for patients with neuromuscular di seases emphasize muscle strength, but postulate that there is no direct relationship between strength and functional per formance 10,17,19,20 . However, Doglio et al reported that some motor strategies may be adopted to compensate for muscle weakness and postpone wheelchair dependency 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Essa escala já foi proposta como padrão de funcionalidade com finalidades clínicas e de pesquisa, com o qual futuros índices deveriam ser comparados 15 . Apesar de apenas um trabalho em língua inglesa ter empregado essa escala na DMD, os autores concluíram que é um instrumento válido para ser empregado na avaliação das limitações funcionais para atividades da vida diária, também nesses pacientes 16 . Nós encontramos uma correlação elevada e altamente significante entre a atual escala EK traduzida e uma versão do índice de Barthel, de uso corrente em serviços de neurologia brasileiros.…”
Section: Discussionunclassified
“…Nair, et al 2 used the Barthel Index 7 to assess ADL in 31 children with DMD, and our group 3 measured the FIM SM in 27 children. The FIM SM is a standardized functional instrument widely used to assess various disabling conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the important goals of patient management is the maintenance of ADL as long as possible. However, only a few reports investigating ADL in patients with DMD have used valid and reliable instruments, 2,3 and no study includes patients aged 15 and older, despite the fact that many patients now survive into adulthood. The aim of this study was to use the Functional Independence Measure (FIM SM ), 4, 5 a validated functional instrument, to assess disabilities in patients with DMD over a wide age range and to analyze the percent of independence associated with each FIM SM item.…”
Section: Introductionmentioning
confidence: 99%